Axis I Psychopathology and the Perpetration of Intimate Partner Violence. Issue 3 (3rd July 2013) - Crane, Cory A.; Hawes, Samuel W.; Devine, Susan; Easton, Caroline J.
<x xml:space="preserve">Abstract</x> Objectives Initial evidence suggests that individuals with specific psychiatric conditions may perpetrate intimate partner violence (IPV) at greater frequency than nondiagnosed comparison samples. The present investigation examined the relationship between IPV and specific clinical diagnoses. Method The current investigation utilized data provided by 190 (34% female) adult offenders during court‐mandated substance use evaluations to investigate the incidence of past‐year IPV among samples of dually diagnosed (bipolar, posttraumatic stress disorder [PTSD], and attention deficit‐hyperactivity disorder [ADHD]) clients relative to 3 comparison samples matched on substance use and sociodemographic variables. Results Bipolar and PTSD diagnosed participants were more likely to perpetrate IPV than matched comparison and ADHD participants. Bipolar and PTSD diagnosed participants were equally likely to perpetrate IPV, as were ADHD and matched comparison samples. Conclusions The frequency of IPV perpetration among bipolar and PTSD diagnosed clients may complicate interpersonal and relationship functioning. The development of integrated treatments for IPV and underlying psychopathology is recommended.